(untitled) (Discourse of Law and Administration, 2023)
Health insurance contribution as a public levy was a subject of several changes during last period of time under the so-called “Polski Ład” (“Polish Deal”) reforms. Still this levy for some time now demonstrated a tendency to differ from the theoretical backgrounds of public contribution, even considering the specific of the latter. Taking into the account the health insurance contribution structure, its aim and functions some new insights on the issue seem to be possible. Expanding compulsory and commonality of the public health insurance, cancelling the link between the health services from the public health insurance and the obligation to pay the contribution or, last but not least, using the health care contribution by the state as a mean to fund its public tasks in the field of health care in a broad sense (including also the non-insured or the services from beyond the insurance scope) diverges the said levy from its model even more than currently observed in the doctrine. The health care insurance contribution likely tends to shift from “the public contribution with exceptions” into a so-called specific tax – a levy from which the proceeds are used to finance certain expenditure, in this case: public tasks in the field of the health care.